2θ-Burster for Rhythm-Generating Circuits - Kelley, Aaron; Shilnikov, Andrey (Frontiers in Applied Mathematics and Statistics, 2020)
We propose and demonstrate the use of a minimal $2θ$ model for endogenous bursters coupled in 3-cell neural circuits. This $2θ$ model offers the benefit of simplicity of designing larger neural networks along with an acute reduction on the computation cost.